Analisis Biaya Pembangunan Site Facilities Proyek Revetment dan Retaining Wall Dermaga Benoa - I Gede Bambang Wahyudi; Kadek Adi Parthama; I Wayan Sujahtra; Ni Kadek Sri Ebtha Yuni; Ni Putu Indah Yuliana (Universitas Batanghari Jambi, 2023)
Process of a construction project is knowing how much a building will cost. Like the main building, the project site facilities also require costs that are not included in the direct financing of the project. The goal is to provide detailed information on the cost of building site facilities and to serve as reference material for the preparation of RAB site facilities. Implemented in the Revetment dan Retaining Wall Harbor Benoa project, the survey it was found that this project had built a number of temporary facilities but did not clearly detail the cost requirements. The research used descriptive quantitative methods and data collection in the form of surveys, observations and interviews. Survey to measure temporary buildings at the project site and find unit prices of tools, materials and labor at shops or foremen around the project area. Observation observes the layout of the building which will be outlined in the field layout drawing.An interview with the project manager was conducted to find out the total cost of the project and the costs incurred by the contractor for construction. Data analysis using Microsoft Excel by entering all components to be analyzed. Based on the results, it is concluded that the site facilities that are built are the contractor's office, health room, motorcycle and car parking, workers' toilets, directors' and consultants' offices, LAB rooms, cement and plywood warehouses, mechanical warehouses, security and K3 posts, workers' beds, trash bins, and water reservoirs. The comparison of site facilities cost to contract is 0.253%.